Assessment of the impact of family physicians in the district health system of the Western Cape, South Africa - Meyer Swanepoel; Bob Mash; Tracey Naledi (AOSIS, 2014)
Background: In 2007, South Africa made family medicine a new speciality. Family physicians that have trained for this new speciality have been employed in the district health system since 2011. The aim of the present study was to explore the perceptions of district managers on the impact of family physicians on clinical processes, health system performance and health outcomes in the district health system (DHS) of the Western Cape. Methods: Nine in-depth interviews were performed: seven with district managers and two with the chief directors of the metropolitan and rural DHS. Interviews were recorded, transcribed and analysed using the ATLAS-ti and the framework method. Results: There was a positive impact on clinical processes for HIV/AIDS, TB, trauma, noncommunicable chronic diseases, mental health, maternal and child health. Health system performance was positively impacted in terms of access, coordination, comprehensiveness and efficiency. An impact on health outcomes was anticipated. The impact was not uniform throughout the province due to different numbers of family physicians and different abilities to function optimally. There was also a perception that the positive impact attributed to family physicians was in the early stages of development. Unanticipated effects included concerns with their roles in management and training of students, as well as tensions with career medical officers. Conclusion: Early feedback from district managers suggests that where family physicians are employed and able to function optimally, they are making a significant impact on health system performance and the quality of clinical processes. In the longer term, this is likely to impact on health outcomes.